Problematika Guru Bahasa Arab Dalam Mengimplementasikan Kurikulum Merdeka Di Madrasah: Kajian Literatur Sistematis - Nurlinda Nurlinda; Hikmatul Lailaa (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study presents a systematic literature review of twenty articles (2022–2025) to identify and synthesize problems faced by Arabic language teachers in implementing the Merdeka Curriculum in madrasahs. A systematic literature review approach with thematic content analysis was employed to extract and categorize findings from selected studies. The results show that implementation problems are systemic and multidimensional, consisting of thirteen themes: teacher competence (80%), lesson planning (70%), instructional implementation (70%), assessment (60%), teaching materials (50%), facilities and infrastructure (50%), technology use (40%), student characteristics (40%), student motivation (30%), administrative workload (30%), institutional support (30%), character integration (20%), and textbook relevance (20%). The synthesis indicates that low teacher competence is the main root problem, affecting planning, instruction, and assessment practices. However, institutional, infrastructural, and learner-related factors also contribute to implementation challenges. Findings also reveal contextual variation across regions, indicating that curriculum implementation is highly dependent on local conditions. This study recommends strengthening teacher competence, improving teaching materials, reducing administrative burdens, enhancing leadership support, and developing context-responsive learning strategies to improve the effectiveness of the Merdeka Curriculum in madrasahs.